ANALISIS AKUMULASI BIAYA PROSES SEBAGAI PENENTU TARGET LABA PADA AYI COLLECTION - eko narto; Muh Hasan; Risa Tria Amanda (Universitas Muhammadiyah Tangerang, 2020)
AbstractThe level of the break even point in this study is used to analyze the achievement of the profit target planned by the Ayi Collection. From the results of the Break event point analysis, it is found that the break-even point occurs in sales of 17,249,307 or 93 units. Based on the results of research and analysis, in 2020 the company's total sales amounted to Rp. 795,500,000 and the company's net profit was Rp. .205,151,691.35. This shows that Ayi Collection's profit exceeds or is above the break-even point. The company targets to increase its profit by 50% by 2020 from net sales. the results of calculations using the break-even point resulted in 622 pcs with sales of Rp. 115,070,000 and a profit of Rp. 25,786,050.19. In this research, Ayi collection has reached the specified profit target which has a difference in production units of 3,678 pcs, a sales difference of Rp. 680,430,000 and a profit difference of Rp. 179,365,641.16